PERCEPTIONS OF DEEP LEARNING AMONG EFL STUDENTS IN INDONESIAN HIGHER EDUCATION: INSIGHTS FROM A THEMATIC STUDY - Farikah, Farikah; Ekawati, Mursia; Mazid , Sukron; Mulyani, Mimi; Winarsih, Dwi; Andini, Jihan Widya (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2025)
This research is motivated by the relevance of the deep learning approach, which emphasizes in-depth understanding, active engagement, and application of knowledge, in line with the demands of 21st-century education and the Freedom to Learn policy. However, students' perceptions of this approach, as the primary subjects of learning, are still limited in Indonesia. Therefore, this study focuses on exploring the perceptions of English as a Foreign Language (EFL) students regarding the implementation of deep learning in higher education. Using a qualitative approach, data were collected through open-ended interviews with 105 sixth-semester students. The data were then analyzed using thematic analysis. The analysis revealed four main themes of student perception: (1) the importance of meaningful understanding beyond mere memorization, (2) the development of critical and reflective thinking, (3) the need for active learner involvement, and (4) the significance of applying knowledge in real-world contexts. These findings indicate that students understand the essence of deep learning and consider it crucial for relevant and applicable learning. It is concluded that students have positive perceptions and support the deep learning approach, indicating the need for student-centered learning design to optimize the potential of this approach. ABSTRAKPenelitian ini dilatarbelakangi oleh relevansi pendekatan deep learning yang menekankan pemahaman mendalam, keterlibatan aktif, dan aplikasi pengetahuan, sejalan dengan tuntutan pendidikan abad ke-21 dan kebijakan Merdeka Belajar. Namun, persepsi mahasiswa sebagai subjek utama pembelajaran terhadap pendekatan ini masih terbatas dikaji di Indonesia. Oleh karena itu, penelitian ini berfokus untuk mengeksplorasi persepsi mahasiswa English as a Foreign Language (EFL) terhadap implementasi deep learning di perguruan tinggi. Menggunakan pendekatan kualitatif, data dikumpulkan melalui wawancara terbuka terhadap 105 mahasiswa semester enam. Data tersebut kemudian dianalisis menggunakan analisis tematik. Hasil analisis mengungkap empat tema utama persepsi mahasiswa: (1) pentingnya Pemahaman yang Bermakna bukan sekadar hafalan, (2) pengembangan Berpikir Kritis dan Reflektif, (3) perlunya Keterlibatan Aktif Pembelajar, dan (4) signifikansi Penerapan Pengetahuan dalam konteks nyata. Temuan ini menunjukkan bahwa mahasiswa memahami esensi deep learning dan menganggapnya penting untuk pembelajaran yang relevan dan aplikatif. Disimpulkan bahwa mahasiswa memiliki persepsi positif dan mendukung pendekatan deep learning, yang mengindikasikan perlunya desain pembelajaran yang berpusat pada mahasiswa untuk mengoptimalkan potensi pendekatan ini.